PENGARUH DIGITAL MARKETING DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN DI KOPI TELU CITRALAND SURABAYA - Shaktiadjie Dewondanu Kusnarto Putro; Yanus Sumitro; Muhammad Hafis hasan; Mohamad Fadlli Romadhon (Jurnal Projemen UNIPA, 2025)
This study aims to analyze the influence of digital marketing and word of mouth on purchasing decisions at KopiTelu Citraland Surabaya. The subjects in this study were consumers who made purchases at Kopi Telu Citraland Surabaya. The sample in this study was 100 customers of Kopi Telu Citraland Surabaya. This type of research is quantitative and uses a questionnaire data collection technique. Data analysis in this study used the classical assumption test and hypothesis test. The results of this study indicate that digital marketing has a positive and significant effect on purchasing decisions at Kopi Telu Citraland Surabaya. Word of Mouth has a positive and significant effect on purchasing decisions at Kopi Telu Citraland Surabaya. Digital marketing and word of mouth simultaneously have a positive and significant effect on purchasing decisions at Kopi Telu Citraland Surabaya.